The implementation of vocabulary teaching technique at Darawittaya Islamic Boarding School in Thailand (Conference on English Language Teaching, 2023)
Vocabulary teaching techniques are beneficial for learning English because it is one of the key processes in mastering the four skills. The researcher focused on teaching vocabulary by using techniques such as beginner, intermediate and advanced techniques at Darawittaya Islamic Boarding School in Thailand, to learn how the process of vocabulary technique was implemented by the teacher. The design of this study is qualitative methods with the aim to identify the vocabulary technique implemented in Darawittaya Islamic Boarding School in Thailand. The study is divided into two parts: vocabulary lesson (after sunrise) and review (before bed). To collect data, the researchers conducted observations, interviews, and records. In this study researcher using an open-ended approach to theobservation, the researcher observes the study subject and location. This type uses non-participants where the researcher just came and recorded the learning. The Researchers used open-ended questions and recorded  interviews. The teaching techniques used at Darawittaya Islamic Boarding School, such as showing the meaning of words, using real objects, using commands and demonstrations by beginner technique, using simple English to show the meaning of words, seeing a word in a sentence, and the value of games for vocabulary learning by intermediate technique.